Carbonaceous material for sintering and method for producing sintered ore

JP2025025142APending Publication Date: 2025-02-21NIPPON STEEL CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023129642
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-21

Smart Images

  • Figure 2025025142000001_ABST
    Figure 2025025142000001_ABST
Patent Text Reader

Abstract

To reduce the emission amount of fine dust generated when sintered ore is produced.SOLUTION: A carbonaceous material for sintering is used in the production of sintered ore and comprises a predetermined carbonaceous material and a lime-based raw material. The predetermined carbonaceous material has an atomic ratio of hydrogen to carbon (H / C) of 0.19 or more and a volatile content of 15 mass% or less. The lime-based raw material adheres to the predetermined carbonaceous material. The CaO concentration in the carbonaceous material for sintering is 5 mass% or more. The CaO concentration can be 5 mass% or more and 20 mass% or less. The carbonaceous material for sintering can be used alone or together with other carbonaceous materials to produce sintered ore.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a carbonaceous material for sintering used in the production of sintered ore, and a method for producing sintered ore using the carbonaceous material for sintering. [Background technology]

[0002] In Patent Document 1, in the production of sintered ore, a surface-coated carbonaceous material is included in a coal blend as a sintering fuel. Here, the surface-coated carbonaceous material is a carbonaceous material that is coated on the surface of the carbonaceous material with a coating material containing 36 mass% or more of Ca derived from a lime-based raw material at a ratio of more than 2 mass% and less than 50 mass% of the carbonaceous material. By using this surface-coated carbonaceous material, the generation of NOx during the production of sintered ore is suppressed.

[0003] In Patent Document 2, in a method for producing sintered ore in which granulated raw materials are fired using a surface-coated carbonaceous material, the composition of the coating of the surface-coated carbonaceous material is set to CaO / (CaO+FeO) of 0.1 to 0.6. By using this surface-coated carbonaceous material, the generation of NOx in the low temperature range is suppressed.

[0004] In Patent Document 3, a carbonaceous material for sintering having a CaO concentration of 4 to 30 mass % is produced by adhering a lime-based raw material to char produced by carbonizing coal having a Roga index of 10 or less. By using this carbonaceous material for sintering, it is possible to reduce the amount of NOx emissions generated when producing sintered ore. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2011 / 129388 [Patent Document 2] JP 2015-086419 A [Patent Document 3] JP 2021-161529 A Summary of the Invention [Problem to be solved by the invention]

[0006] When sintered ore is produced, fine dust is discharged from the sintering machine. However, the inventors of the present application focused on the volatile matter and the atomic ratio of hydrogen atoms to carbon atoms (H / C) in the carbon material to which the lime-based raw material is adhered, and found that the amount of fine dust discharged could be reduced, which led to the completion of the present invention.

[0007] Patent Documents 1 to 3 do not recognize at all that the volatile matter and H / C of a carbonaceous material for sintering, which is a carbonaceous material to which a lime-based raw material is adhered, affect the amount of fine dust discharged. [Means for solving the problem]

[0008] The first invention of the present application is a carbonaceous material for sintering used in the production of sintered ore, which includes a predetermined carbonaceous material and a lime-based raw material. The predetermined carbonaceous material has an atomic ratio of hydrogen atoms to carbon atoms (H / C) of 0.19 or more and a volatile content of 15 mass% or less. The lime-based raw material is adhered to the predetermined carbonaceous material. The CaO concentration in the carbonaceous material for sintering is 5 mass% or more.

[0009] The CaO concentration in the carbonaceous material for sintering may be 5% by mass or more and 20% by mass or less. As the lime-based raw material, quicklime may be used.

[0010] The method for producing sintered ore according to the second aspect of the present invention produces sintered ore by using the carbonaceous material for sintering according to the first aspect of the present invention alone, or by using the carbonaceous material for sintering according to the first aspect of the present invention together with other carbonaceous materials. As the other carbonaceous materials, carbonaceous materials to which no lime-based raw material is attached and having an H / C ratio of less than 0.19 can be used. Effect of the Invention

[0011] By using the carbonaceous material for sintering according to the present invention, it is possible to reduce the amount of fine dust discharged during the production of sintered ore. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram of a sintering test apparatus. [Diagram 2] FIG. 2 is a schematic diagram of an aerosol measurement section in a sintering test apparatus. [Diagram 3] FIG. 1 is a diagram showing the relationship between the H / C of the carbonaceous material to which the lime-based raw material adheres and the concentration of fine dust discharged during the production of sintered ore. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In this embodiment, by producing sintered ore using a carbonaceous material for sintering described later, it is possible to reduce the amount of fine dust discharged during the production of sintered ore (sintering step) (in other words, the fine dust concentration described later). A specific description will be given below.

[0014] (Carbon for sintering) The carbonaceous material for sintering is composed of a predetermined carbonaceous material and a lime-based raw material adhered to the predetermined carbonaceous material. The predetermined carbonaceous material has an atomic ratio of hydrogen atoms to carbon atoms (H / C) of 0.19 or more and a volatile content of 15 mass% or less. The CaO concentration in the carbonaceous material for sintering is 5 mass% or more.

[0015] Examples of the carbonaceous material for sintering include a coated type carbonaceous material for sintering in which the surface of the carbonaceous material for sintering is coated with a lime-based raw material, and a mixed type carbonaceous material for sintering in which a predetermined carbonaceous material and a lime-based raw material are mixed. In both the coated type and the mixed type, the lime-based raw material is attached to the predetermined carbonaceous material.

[0016] In the coated carbonaceous material for sintering, the inside of the particles forming the carbonaceous material for sintering is composed of a specific carbonaceous material, and the surface layer of the particles forming the carbonaceous material for sintering is composed of a lime-based raw material. Here, the lime-based raw material does not need to cover the entire surface of the carbonaceous material for sintering, and may cover only a part of the surface of the carbonaceous material for sintering. In the mixed type carbonaceous material for sintering, the specific carbonaceous material and the lime-based raw material are mixed in the entire particle forming the carbonaceous material for sintering.

[0017] The coated carbonaceous material for sintering can be produced by granulating a specific carbonaceous material together with a lime-based raw material, and adhering the lime-based raw material to the surface of the carbonaceous material particles. The mixed carbonaceous material for sintering can be produced by mixing a specific carbonaceous material and a lime-based raw material having a smaller particle size than the specific carbonaceous material used in the coated carbonaceous material for sintering, and granulating the mixture. In producing the carbonaceous material for sintering, a granulator such as a drum mixer or a pan pelletizer can be used. Here, one type of granulator can be used, or multiple types of granulators can be used in combination. In addition, in order to make it easier to adhere the lime-based raw material to the specific carbonaceous material, it is preferable to add moisture during the production of the carbonaceous material for sintering.

[0018] When producing the carbonaceous material for sintering, the blending ratio of the predetermined carbonaceous material and the lime-based raw material can be appropriately determined. The blending ratio of the predetermined carbonaceous material and the lime-based raw material can be determined so that the CaO concentration in the carbonaceous material for sintering is 5 mass% or more, but the blending ratio of the lime-based raw material may be set higher than the target value in anticipation of the occurrence of lime-based raw material that adheres to the granulator and becomes a loss during granulation of the carbonaceous material for sintering. The blending ratio of the predetermined carbonaceous material and the lime-based raw material can be changed depending on whether it is a coated type or a mixed type.

[0019] (Specified carbon material) As described above, the specified carbonaceous material is a carbonaceous material having an H / C of 0.19 or more and a volatile content of 15 mass% or less. Anthracite and char tend to have a volatile content of 15 mass% or less. As the raw material for the specified carbonaceous material, one type of coal can be used, a mixed coal of two or more types of coal can be used, or a mixed coal of multiple coals of the same type but with different coal properties (proximate analysis values ​​and elemental analysis values) can be used.

[0020] H / C is calculated based on the following formula (1).

number

[0021] In the above formula (1), H / C is the atomic ratio of hydrogen atoms to carbon atoms [-], H_ea is the elemental analysis value of hydrogen [mass%], and C_ea is the elemental analysis value of carbon [mass%]. Here, the elemental analysis values ​​H_ea and C_ea can be measured according to the JIS M8819 standard. Meanwhile, the volatile content can be measured according to the JIS M8812 standard.

[0022] The particle size of the predetermined carbonaceous material can be appropriately determined, and can be, for example, the particle size (10 mm or less) of the carbonaceous material used in the production of normal sintered ore.

[0023] (lime-based raw material) Examples of lime-based raw materials include limestone (CaCO3), quicklime (CaO) made by burning limestone, and slaked lime (Ca(OH)2) made by hydrating quicklime. These lime-based raw materials may be used alone or in combination of multiple types. When using one type of lime-based raw material, quicklime can be used, and when using multiple types of lime-based raw materials, quicklime can be used as the main component.

[0024] The amount of the lime-based raw material may be adjusted so that the CaO concentration in the carbonaceous material for sintering is 5% by mass or more. When quicklime is used as the lime-based raw material, the content of quicklime in the carbonaceous material for sintering is the CaO concentration. On the other hand, when limestone or slaked lime is used as the lime-based raw material, the value converted from the amount of the lime-based raw material to the CaO concentration may be 5% by mass or more. The CaO concentration in the carbonaceous material for sintering is preferably 5% by mass or more and 20% by mass or less.

[0025] When producing a coated carbonaceous material for sintering, it is preferable to set the particle size of the lime-based raw material smaller than the particle size of the predetermined carbonaceous material. This allows the lime-based raw material to be efficiently attached to the surface of the predetermined carbonaceous material, making it easier to coat the surface of the predetermined carbonaceous material with the lime-based raw material. As described above, when the particle size of the predetermined carbonaceous material is 10 mm or less, it is preferable to set the particle size of the lime-based raw material to 0.25 mm or less.

[0026] When producing a mixed type carbonaceous material for sintering, it is preferable to make the particle size of the predetermined carbonaceous material and the particle size of the lime-based raw material equal so that the predetermined carbonaceous material and the lime-based raw material can be easily mixed. For example, the particle size of the predetermined carbonaceous material and the particle size of the lime-based raw material can both be 0.25 mm or less.

[0027] (Other carbonaceous materials) As the carbonaceous material used in the production of sintered ore, the sintering carbonaceous material of this embodiment can be used alone, but other types of carbonaceous materials can also be used in addition to this sintering carbonaceous material. The other carbonaceous material can be appropriately selected, and for example, a carbonaceous material to which no lime-based raw material is attached, a carbonaceous material having an H / C ratio of less than 0.19, or a carbonaceous material having a volatile content of more than 15 mass% can be used. The other carbonaceous material may be one type or multiple types. For example, coke powder can be used as the other carbonaceous material.

[0028] When using a specified carbonaceous material in combination with other carbonaceous materials, by adhering the lime-based raw material only to the specified carbonaceous material having an H / C ratio of 0.19 or more and a volatile matter content of 15 mass% or less, rather than adhering the lime-based raw material to all of the carbonaceous materials, it is possible to effectively reduce the emission of fine dust while suppressing the increase in costs associated with the use of the lime-based raw material.

[0029] When the sintering carbonaceous material and other carbonaceous materials are used in combination, the blending ratio M1 [mass%] of the sintering carbonaceous material and the blending ratio M2 [mass%] of the other carbonaceous materials can be appropriately determined. Here, the blending ratio M1 is the ratio of the blending amount of the sintering carbonaceous material to the total mass of all carbonaceous materials (including the sintering carbonaceous material and other carbonaceous materials), and the blending ratio M2 is the ratio of the blending amount of the other carbonaceous materials to the total mass of all carbonaceous materials (including the sintering carbonaceous material and other carbonaceous materials). If the blending ratio M1 of the sintering carbonaceous material is too low, it may be difficult to obtain the effect of this embodiment (reduction in the amount of fine dust emissions), so it is preferable to set the blending ratio M1 to 10 mass% or more.

[0030] (Sintered Ore Manufacturing Method) The carbonaceous material for sintering according to the present embodiment can be mixed with iron ore and auxiliary materials and heated to produce sintered ore. As the iron ore used as the raw material for sintered ore, one type of iron ore or multiple types of iron ore can be used. Examples of the auxiliary materials include limestone, quicklime, peridotite, and serpentine. The raw materials for sintered ore can include return ore in addition to the iron ore, auxiliary materials, and carbonaceous material for sintering.

[0031] The raw materials for sintering are granulated and then charged into a sintering machine through a hopper. This forms a raw material packed bed in the sintering machine, and the upper part of the raw material packed bed is ignited, causing the raw material packed bed to combust and produce a sintered cake. The sintered cake is crushed and sized to obtain sintered ore of a desired particle size.

[0032] In the process of granulating the raw materials for sintered ore, water is generally added to the raw materials before granulation. By adding water to the raw materials before granulation, the water acts as a binder, causing relatively fine particles to adhere to the periphery of relatively coarse particles. This increases the apparent particle size of the raw materials, and when the raw materials are loaded into a sintering machine, the porosity and pore size of the raw material packed bed increase, improving air permeability. Improved air permeability speeds up the sintering process, and also improves the productivity of sintered ore.

[0033] When the carbonaceous material for sintering according to this embodiment is mixed and granulated with other blended raw materials at the same time, the lime-based raw material contained in the carbonaceous material for sintering according to this embodiment may be separated from the carbonaceous material for sintering during mixing and granulation. In this case, it becomes difficult to obtain the effect of this embodiment (reduction in the amount of fine dust emission).

[0034] To solve the above-mentioned problems, the sintering carbonaceous material can be added later. The latter addition means that the sintering carbonaceous material is not added at the beginning of the process of mixing and granulating the blended raw materials for sintered ore, but is added in the middle of completing the above-mentioned process. For example, it is preferable that the time from the start of the above-mentioned process to the addition of the sintering carbonaceous material is 80% or more and 95% or less of the total process time. The latter addition includes the case where the entire amount of the sintering carbonaceous material is added later, and the case where a part of the total amount of the sintering carbonaceous material is added later. When a part of the sintering carbonaceous material is added later, the remaining sintering carbonaceous material can be mixed simultaneously with the raw materials except for the sintering carbonaceous material. EXAMPLES

[0035] EXAMPLES Hereinafter, examples of the present invention will be described. However, the present invention is not limited to the examples described below.

[0036] (Type of charcoal) Anthracite A to J and char A to F shown in Table 1 below were prepared as carbonaceous materials. Table 1 below shows analytical values ​​(proximate analysis values ​​and elemental analysis values) and H / C for each carbonaceous material and coke breeze for comparison. As shown in Table 1 below, anthracite A to J and char A to F had a volatile matter content of 15 mass% or less, and anthracite A to E and char A to E had an H / C ratio of 0.19 or more.

[0037] [Table 1]

[0038] (Manufacturing carbon materials for sintering) The carbonaceous material (each of the anthracites A to J or each of the chars A to F) and quicklime (lime-based raw material) equivalent to 20% by mass of the carbonaceous material were put into a kneader and kneaded for 3 minutes while adding water. Here, the amount of water added was 24% by mass with respect to the total mass of the carbonaceous material and quicklime. After kneading, the mixture was granulated for 5 minutes using a pan pelletizer to produce carbonaceous material with quicklime attached to each of the carbonaceous materials (each of the anthracites A to J or each of the chars A to F) (hereinafter referred to as "adhered carbonaceous material"). In addition to the above-mentioned adhered carbonaceous materials, carbonaceous material without quicklime attached (each of the anthracites A to J or each of the chars A to F, hereinafter referred to as "non-adhered carbonaceous material") was also prepared as the carbonaceous material to be used in the sintering test described later.

[0039] (Sintering test) The concentration of fine dust was measured by performing a sintering process using a small-sized experimental facility (hereinafter referred to as the "pot") made from a sintering machine. The diameter of the pot was 300 mm, and the thickness of the pot was 600 mm. The suction pressure of the combustion gas during the sintering process was set to 15.0 kPa.

[0040] The raw materials used in the sintering test are shown in Table 2 below.

[0041] [Table 2]

[0042] As the iron ore, iron ores of brands A to F were prepared. The blending ratios [mass%] of these iron ores are as shown in Table 2 above. As the auxiliary materials, limestone, quicklime, and peridotite were prepared. The blending ratios [mass%] of these auxiliary materials are as shown in Table 2 above. On the other hand, return ore and carbonaceous material were blended with the iron ore and the auxiliary materials. Here, as the carbonaceous material, the adhering carbonaceous material produced as described above and the non-adhering carbonaceous material to which quicklime was not attached (each of anthracites A to J or each of chars A to F) were used, respectively.

[0043] The blending ratio of the return ore was 15% by mass based on the total mass of the iron ore and auxiliary materials. The blending ratio of the carbonaceous material for sintering was adjusted so that the amount of coke fines and fixed carbon was equal to 4.5% by mass based on the total mass of the iron ore and auxiliary materials. The particle size distribution of the carbonaceous material is as shown in Table 3 below.

[0044] [Table 3]

[0045] The raw materials for sintering other than the carbonaceous material (iron ore, auxiliary raw materials, and return ore) were put into a drum mixer (diameter 1 m, rotation speed 23 rpm) and mixed for 1 minute. Next, water was added to the drum mixer so that the target moisture content was 7.5 mass% (excl. number), and the mixture in the drum mixer was granulated for a certain period of time. Next, the mixture in the drum mixer was mixed (granulated) for an additional 4 minutes. Here, the carbonaceous material was added 30 seconds before the 4 minutes had elapsed. When adding the carbonaceous material, the drum mixer was temporarily stopped.

[0046] Hereinafter, the method for measuring the fine dust concentration will be described with reference to Figures 1 and 2. Figure 1 is a schematic diagram of a sintering test apparatus, and Figure 2 is a schematic diagram of an aerosol measurement section in the sintering test apparatus.

[0047] The sintering test equipment 100 comprises a pot 1, a suction tube 2, a blower 3, an exhaust pipe 4, a chimney 5 and an aerosol measuring unit 10. The pot 1 is a cylindrical container for sintering the sintering raw materials, with an open upper end and a grate (not shown) at the lower end. The suction tube 2 is a tube for sucking sintering exhaust gas from the pot 1 during sintering. One end of the suction tube 2 is connected to the lower end of the pot 1. The blower 3 is connected to the other end of the suction tube 2 and applies negative pressure to the suction tube 2. The exhaust pipe 4 is a tube for guiding the sintering exhaust gas from the blower 3 to the chimney 5, and the lower end of the exhaust pipe 4 is connected to the blower 3. The chimney 5 is connected to the upper end of the exhaust pipe 4 and exhausts the sintering exhaust gas into the atmosphere.

[0048] The aerosol measurement unit 10 measures the concentration of fine dust contained in the sintering exhaust gas. As shown in Fig. 2, the aerosol measurement unit 10 includes an introduction pipe 11, a diluter (DI-1000, manufactured by Dekati) 12, a sensor (2070H, manufactured by PALAS) 13, an aerosol spectrometer (Prom2000, manufactured by PALAS) 14, a dryer 15, a filter 16, a flowmeter 17, and a suction pump 18.

[0049] The introduction pipe 11 is a pipe for sucking the sintering exhaust gas into the aerosol measurement section 10, and is disposed in the flow path of the sintering exhaust gas in the discharge pipe 4. The introduction pipe 11 is preferably provided downstream of the flow path of the sintering exhaust gas from the blower 3 (see FIG. 1). If the introduction pipe 11 is provided in the suction pipe 2 located upstream of the sintering exhaust gas flow path from the blower 3, the sintering exhaust gas introduced from the introduction pipe 11 is likely to condense due to moisture generated during sintering. In addition, it becomes difficult to adjust the flow rate of the sintering exhaust gas introduced into the aerosol measurement section 10 due to the influence of the negative pressure from the blower 3. Therefore, the introduction pipe 11 is preferably provided downstream of the flow path of the sintering exhaust gas from the blower 3.

[0050] The diluter 12 dilutes a certain amount of the sintering exhaust gas introduced from the introduction pipe 11 with air to reduce the fine dust concentration. In this embodiment, the sintering exhaust gas was diluted 8 times. When the fine dust concentration in the sintering exhaust gas exceeds the measurement limit concentration of the aerosol spectrometer 14, it is preferable to use the diluter 12. Air supplied to the diluter 12 is supplied from a compressor 21. While the air moves from the compressor 21 to the diluter 12, moisture in the air is removed by a dryer 22 to prevent condensation, the pressure of the air is adjusted by a regulator 23, and the temperature of the air is adjusted by a heater 24. In addition, when the moisture content in the sintering exhaust gas is high, the periphery of the diluter 12 may be heated by a heater (not shown) to further prevent condensation.

[0051] The sensor 13 detects fine dust contained in the sintering exhaust gas. The sensor 13 is disposed in a flow path through which the sintering exhaust gas containing fine dust flows and in an optical path through which light for detecting the fine dust passes. The aerosol spectrometer 14 measures the concentration of the fine dust. Specifically, the aerosol spectrometer 14 irradiates light into the flow path of the sintering exhaust gas and measures the fine dust concentration by utilizing the phenomenon in which the irradiated light is scattered by the fine dust. The dryer 15 removes moisture from the sintering exhaust gas that has passed through the sensor 13. The filter 16 captures the fine dust contained in the sintering exhaust gas that has passed through the dryer 15. The flowmeter 17 measures the flow rate of the sintering exhaust gas that has passed through the filter 16. The suction pump 18 generates a suction force for introducing the sintering exhaust gas from the exhaust pipe 4 to the aerosol measurement unit 10.

[0052] The aerosol measuring section 10 is not limited to the configuration shown in FIG. 2 as long as it has a configuration capable of measuring the concentration of fine dust contained in the sintering exhaust gas.

[0053] In the sintering test using the sintering test apparatus 100, a sintering test is performed using raw materials for sintering. The sintering test was performed in the same manner as the known pot sintering test (see, for example, "Tetsu to Hagane Vol. 88 (2002) No. 1, pp. 16-22"). The fine dust concentration in the sintering exhaust gas generated during the sintering test was measured by the aerosol measuring unit 10. The sintering test was performed in two cases: when an adhesive carbonaceous material (carbonaceous material with lime attached thereto) was used as the carbonaceous material, and when a non-adhesive carbonaceous material (i.e., carbonaceous material without lime attached thereto) was used as the carbonaceous material.

[0054] It is preferable to measure the fine dust concentration continuously. This allows a higher capture rate of fine dust and a higher measurement accuracy of the fine dust concentration compared to a batch process in which the fine dust in the sintering exhaust gas is captured by a filter or the like and then the fine dust concentration is measured. In addition, the change over time in the fine dust concentration from the start to the end of sintering can also be measured.

[0055] The fine dust concentration can be expressed, for example, by the number of fine dust particles (particles / ml) per unit volume of the sintering exhaust gas. Since the fine dust concentration varies (changes over time) during sintering, it is preferable to use an average value obtained by averaging a number of fine dust concentrations measured from the start to the end of sintering. Note that the fine dust concentration is not limited to the average value, and for example, it is also possible to focus on the fine dust concentration measured at a specific timing during sintering, or on the highest fine dust concentration during sintering.

[0056] The sintering exhaust gas contains dust derived from iron ore and dust derived from carbonaceous materials, but the particle size (diameter) of the dust derived from carbonaceous materials tends to be smaller than that of the dust derived from iron ore, with the maximum particle size being 1 μm or less. In this example, the dust derived from carbonaceous materials (fine dust) was the measurement target.

[0057] The measurement results of fine dust concentration are shown in Figure 3. In Figure 3, the vertical axis is the fine dust concentration [×10 3 The horizontal axis is H / C [-]. Figure 3 shows the fine dust concentration (CaO=20[mass%]) when a sintering test was conducted using an adhesive carbonaceous material (carbonaceous material with lime attached) as the carbonaceous material, and the fine dust concentration (CaO=0[mass%]) when a sintering test was conducted using a non-adhesive carbonaceous material (i.e., carbonaceous material with no lime attached) as the carbonaceous material.

[0058] As described above, the sintering exhaust gas was diluted 8 times by the diluter 12 (see FIG. 2), and therefore the fine dust concentration shown in FIG. 3 is the fine dust concentration when the sintering exhaust gas was diluted 8 times. In addition, the fine dust concentration shown in FIG. 3 was calculated as an average value by averaging multiple fine dust concentrations measured from the start to the end of sintering.

[0059] As can be seen from Fig. 3, when H / C was less than 0.19, the fine dust concentration was the same regardless of whether quicklime (lime-based raw material) was attached to the carbonaceous material (each of the anthracites F to J or char F). On the other hand, when H / C was 0.19 or more, the fine dust concentration (CaO = 20 [mass %]) when using the carbonaceous material (each of the anthracites A to E or each of the chars A to E) with quicklime attached thereto (the carbonaceous material for sintering in the present invention) was significantly lower than the fine dust concentration (CaO = 0 [mass %]) when using the carbonaceous material (each of the anthracites A to E or each of the chars A to E) without quicklime attached thereto.

[0060] As a result, for specified carbonaceous materials (specifically, anthracite A to E and char A to E) with an H / C ratio of 0.19 or more and a volatile content of 15 mass% or less, the amount of fine dust emissions can be reduced by adhering lime-based raw materials.

[0061] Next, the effect of the blending ratio of the lime-based raw material added was confirmed using anthracite B shown in Table 1 above. Lime-based raw materials (quicklime) were prepared with the blending amount adjusted so that the CaO concentration in the carbonaceous material for sintering was 2, 5, 20, and 30 mass%, and carbonaceous materials for sintering were manufactured by adhering each lime-based raw material to anthracite B. Then, in a sintering test, the fine dust concentration was measured by the measurement method described above. The measurement results are shown in Table 4 below. Table 4 below also shows the fine dust concentration when a sintering test was conducted using anthracite B in which the CaO concentration in the carbonaceous material for sintering was 0 mass% (i.e., anthracite B to which no lime-based raw material was attached).

[0062] [Table 4]

[0063] The fine dust concentration when the CaO concentration was 2% by mass was similar to that when the CaO concentration was 0% by mass. On the other hand, when the CaO concentration was 5% by mass or more, the fine dust concentration was reduced compared to when the CaO concentration was 0 or 2% by mass. Therefore, in order to obtain the effect of reducing the fine dust concentration, the CaO concentration should be set to 5% by mass or more.

[0064] On the other hand, according to Table 4, the reduction in the fine dust concentration is not proportional to the increase in the CaO concentration, and the reduction in the fine dust concentration when the CaO concentration is increased from 20% by mass to 30% by mass (0.2=11.0-10.8) is smaller than the reduction in the fine dust concentration when the CaO concentration is increased from 5% by mass to 20% by mass (10.9=21.9-11.0). As mentioned above, the CaO concentration may be 5% by mass or more, but it is considered that the effect of reducing the fine dust concentration is more likely to converge as the CaO concentration is higher. Considering the cost of lime-based raw materials, the upper limit of the CaO concentration can be set to 20% by mass.

[0065] Next, when two types of carbonaceous materials are used in combination to produce sintered ore, the effect of attaching a lime-based raw material to each of the two types of carbonaceous materials was confirmed. The two types of carbonaceous materials used were the fine coke and anthracite B shown in Table 1 above, and the blending ratio of each carbonaceous material was the same (50 mass%, the blending ratio here was based on the mass before the lime-based raw material was attached to each carbonaceous material). In addition, a sintering carbonaceous material was used in which quicklime was attached to anthracite B so that the CaO concentration in the sintering carbonaceous material was 20 mass%.

[0066] The H / C of the coke fines was 0.02 [-], and the H / C of the anthracite B was 0.43 [-] (see Table 1 above). In Example 1, the coke fines was used as is without adhering any lime-based raw materials, and anthracite B with lime-based raw materials attached thereto was used as a carbonaceous material for sintering, and in Example 2, both the coke fines and the anthracite B with lime-based raw materials attached thereto were used. In the comparative example, both the coke fines and the anthracite B were used as is without adhering any lime-based raw materials.

[0067] Sintering tests were carried out using the carbonaceous materials of Examples 1 and 2 and the Comparative Example, and the fine dust concentrations were measured by the above-mentioned measuring method. The measurement results are shown in Table 5 below.

[0068] [Table 5]

[0069] In the case where the lime-based raw material was adhered only to the anthracite B (Example 1) and in the case where the lime-based raw material was adhered to both the coke fines and the anthracite B (Example 2), the fine dust concentration was significantly reduced compared to the case where the lime-based raw material was not adhered to either the coke fines or the anthracite B (Comparative Example). In addition, in the case where the lime-based raw material was adhered only to the anthracite B (Example 1), the fine dust concentration was reduced to the same extent compared to the case where the lime-based raw material was adhered to both the coke fines and the anthracite B (Example 2).

[0070] This shows that when fine coke and anthracite B are used in combination as carbonaceous materials, the fine dust concentration can be reduced by simply attaching a lime-based raw material to only anthracite B, which has an H / C ratio of 0.19 or more. In other words, to reduce the fine dust concentration, it is not necessary to attach a lime-based raw material to fine coke, which has an H / C ratio of less than 0.19, and it is sufficient to simply use the fine coke as is. [Explanation of symbols]

[0071] 100: sintering test equipment, 1: pot, 2: suction pipe, 3: blower, 4: exhaust pipe, 5: chimney, 10: aerosol measurement unit, 11: introduction pipe, 12: diluter, 13: sensor, 14: aerosol spectrometer, 15: dryer, 16: filter, 17: flow meter, 18: suction pump, 21: compressor, 22: dryer, 23: regulator, 24: Heater

Claims

1. A carbonaceous material for sintering used in the production of sintered ore, A predetermined carbonaceous material having an atomic ratio of hydrogen atoms to carbon atoms (H / C) of 0.19 or more and a volatile content of 15 mass% or less; A lime-based raw material adhered to the predetermined carbonaceous material, The carbonaceous material for sintering is characterized in that the CaO concentration in the carbonaceous material for sintering is 5 mass % or more.

2. 2. The carbonaceous material for sintering according to claim 1, wherein the CaO concentration is from 5% by mass to 20% by mass.

3. 2. The carbonaceous material for sintering according to claim 1, wherein the lime-based raw material is quicklime.

4. A method for producing sintered ore, comprising the step of producing sintered ore by using the carbonaceous material for sintering according to any one of claims 1 to 3 alone.

5. A method for producing sintered ore, comprising the step of producing sintered ore by using the carbonaceous material for sintering according to any one of claims 1 to 3 together with other carbonaceous materials.

6. 6. The method for producing sintered ore according to claim 5, wherein the other carbonaceous material is not adhered to the lime-based raw material and has an H / C ratio of less than 0.19.

Citation Information

Patent Citations

  • Method of producing sintered ore

    JP2015086419A

  • Method for producing carbonaceous material for sintering, and method for producing sintered ore

    JP2021161529A

  • Process for production of sintered mineral

    WO2011129388A1